Comparative Analysis of the Impact of the Four Elements of Strategic Plan on Product and Market Development in Zinc Companies - Jafari, Mostafa; Eslami, Mina (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
Objective :This study was to analyze the impact of each of four elements of strategic plan (vision processing, analysis of external environment, inter- organization analysis and strategic control) on product and market development in zinc companies in Zanjan province. Methodology:Based on objective, this was a descriptive - explanatory study, while it could be defined a cross-sectional one based on time. According to the result, it was an applied research and a quantitative and qualitative based on variables. Finally, it was a surveying study according to data collection method. The target population members included 120 CEOs and business managers of companies active in the zinc industry in Zanjan Province, which were evaluated by census method. The data collection tool was a questionnaire and SPSS software was used for data statistical analysis. The hypotheses were also tested using single-sample t-test and ANOVA. Results : The "vision processing or building" does not affect the product and market development, but three factors of "external environment analysis, inter-organizational analysis and strategic control" affect the development of the market and the product of zinc companies. The most effective factor is "strategic control", and the least effective factor is "external environment analysis".